Hubungan Perilaku Simpanan Masyarakat di Perbankan dan Pertumbuhan Ekonomi - Mochtar, Firman (Jurnal Ekonomi dan Pembangunan Indonesia, 2006)
This study shows that an increase in economic funding that comes from saving fund in the banking sector doesn't have a full impact on the slower economic growth in the subsequent period as Keynesian believes. Tests result show that a decrease in public saving in banking sector reflects an increase in the confidence of the economic agents on the future economic prospects which then drives the economic growth. This result is supported by the negative and significant relationship of economic growth and public saving in the form of individual rupiah denominated deposit (time deposits?). Using Permanent Income Hypothesis argument,the result indicates that we can use individual deposit as one of the leading indicators of future economic growth based on significant finding until 2 trimester in the future. On the other hand, positive and significant relationship of economic growth and public saving which is proposed by the Keynesian only applied to rupiah denominated individual and firm demand deposit and individual saving account.